Efektivitas Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Kelas X SMK Muhammadiyah 1 Pekabaru - Nurul Fauziyah; Rahmad Alrian (Jurnal Pendidikan Dirgantara, 2025)
This study aims to analyze the effectiveness of the guided inquiry learning model on student learning outcomes in the science and natural sciences material on differences in characteristics between spaces. The research method used is a literature study by collecting and analyzing various relevant academic sources. Data were collected from journals, books, and previous studies that discuss the guided inquiry learning model and its impact on student learning outcomes. The results of the literature study indicate that the guided inquiry learning model is effective, can improve students' understanding and learning outcomes compared to conventional learning models. This model allows students to be more active in exploring concepts, thinking critically, and developing problem-solving skills. Thus, the guided inquiry learning model can be an effective alternative in science and natural sciences learning to improve student learning outcomes